2012
DOI: 10.21527/2237-6453.2012.21.146-177
|View full text |Cite
|
Sign up to set email alerts
|

Os Conselhos Municipais de Políticas Públicas sob o Olhar da Comunidade: uma Experiência de Extensão Universitária

Abstract: <strong><span style="font-family: &quot;Times New Roman&quot;,&quot;serif&quot;; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Partindo-se da relação entre gestão social e extensão universitária em uma perspectiva freiriana, esse artigo pretende analisar uma iniciativa de extensão enquanto um instrumento para a conscientização da comunidade acerca da importância da participação, bem como para a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
2
0
2
Order By: Relevance
“…Thus, the universalization of social rights, which, to a certain extent, would contribute to the democratic potential of the Councils in debates and negotiations regarding management decisions and the establishment of proposals and guidelines, recognizing the dialogue between users, workers in the field, public institutions and NGOs, may not be occurring in practice, given the tendency to the abstract position of Universalism in the empirical structure of Brazilian values . This has been reported by a number of authors (Oliveira, 2009;Falchetti, 2011;Kronemberger et al, 2012;Alves et al, 2013), who studied the reality of MSAC actions and observed difficulties such as the tendency to fragmentary defense of interests (defending the interests of the ruling group, the NGO in which they work or volunteer, among others); lack of dissemination and information in the community regarding the councils; predominance of political clientele; nonexistence of communication channels between the population and the council; a certain disparity between the representatives of different segments; lack of social coordination and a gap between representatives and the represented, among others.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Thus, the universalization of social rights, which, to a certain extent, would contribute to the democratic potential of the Councils in debates and negotiations regarding management decisions and the establishment of proposals and guidelines, recognizing the dialogue between users, workers in the field, public institutions and NGOs, may not be occurring in practice, given the tendency to the abstract position of Universalism in the empirical structure of Brazilian values . This has been reported by a number of authors (Oliveira, 2009;Falchetti, 2011;Kronemberger et al, 2012;Alves et al, 2013), who studied the reality of MSAC actions and observed difficulties such as the tendency to fragmentary defense of interests (defending the interests of the ruling group, the NGO in which they work or volunteer, among others); lack of dissemination and information in the community regarding the councils; predominance of political clientele; nonexistence of communication channels between the population and the council; a certain disparity between the representatives of different segments; lack of social coordination and a gap between representatives and the represented, among others.…”
Section: Resultssupporting
confidence: 69%
“…The other findings of this study, together with those of other authors who analyzed the dynamics of MSACs (Oliveira, 2009;Falchetti, 2011;Kronemberger et al, 2012;Alves et al, 2013;among others), seem to point in that direction, given that respondents were also conservative, which could compromise the struggle for collective rights, social justice and equality in participation and deliberations, favoring continuation of status quo. On the other hand, the fact that MSAC representatives reject excessive authority and power is a positive aspect for the functioning of Councils.…”
Section: Final Considerationssupporting
confidence: 68%
See 2 more Smart Citations
“…A situação é agravada, na visão dos autores, pela falta de condições efetivas para a realização de um trabalho voluntário, não remunerado, a ser executado, na maior parte das vezes, durante as reuniões e sem um suporte operacional autônomo de qualidade. Além dessas questões, Kronemberguer et al [56] citam a hegemonia do Executivo nas decisões políticas e uma cultura clientelista que ainda predomina no âmbito municipal. Citando vários outros trabalhos, os autores reafirmam que as dificuldades são muitas e alertam que a legislação (de criação dos Conselhos) não assegura a divisão de poder entre o estado e a sociedade nem a democratização do processo.…”
Section: Participação Social E Segurança Alimentar E Nutricionalunclassified